Changing Course of Diabetic Nephropathy in the Pima Indians - Nelson, Robert G. (2008)
Pima Indians from the Gila River Indian Community in Arizona have a high incidence rate of type 2 diabetes, and kidney disease attributable to diabetes is a major cause of morbidity and mortality in this population. Since 1965, each member of the population at least 5 years of age is invited to participate in a research examination every other year. During the past 43 years, the overall incidence of diabetes in the Pima Indians has not changed, but the incidence of diabetes among those less than 15 years of age has increased nearly 6-fold, as an increasing prevalence and degree of obesity in the youth has shifted the onset of diabetes to younger ages. The rising frequency of diabetes in the youth has led, in turn, to the emergence in mid-life of the major complications of diabetes, including kidney disease. On the other hand, the introduction and widespread use of medicines to control blood pressure, reduce hyperglycemia, and block the renin-angiotensin system has lead to improvements in the average blood pressure and glycosylated hemoglobin levels in the diabetic population. These countervailing forces have influenced the course of diabetic nephropathy in a generally favorable direction in the past few years, as evidenced by the decline in the overall incidence of end-stage kidney disease since 1990. A continued increase in the incidence of type 2 diabetes in youth, however, threatens to reverse this trend.